2015
DOI: 10.1016/j.jqsrt.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional axisymmetric formulation of high order spherical harmonics methods for radiative heat transfer

Abstract: a b s t r a c tThe spherical harmonics (P N ) method is a radiative transfer equation solver, which approximates the radiative intensity as a truncated series of spherical harmonics. For general 3-D configurations, NðN þ 1Þ=2 intensity coefficients must be solved from a system of coupled second-order elliptic PDEs. In 2-D axisymmetric applications, the number of equations and intensity coefficients reduces to ðN þ 1Þ 2 =4 if the geometric relations of the intensity coefficients are taken into account. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It was found that while the P3 approximation is significantly more accurate than P1, the P5 approximation yields only a slight improvement in accuracy over P3, which is hardly justifiable regarding the increased computational effort. A simplified formulation for 2D axisymmetric problems, which also involves 2( + 1) 4 ⁄ simultaneous partial differential equations, was presented by Ge et al [50], and also implemented in OpenFOAM. Additional refinements of this work were reported by Ge et al [51] who derived a 2D Cartesian version of the higher-order PN method, extended the boundary conditions to allow for nonblack and mixed diffuse-specular surfaces, and to deal with specified radiative flux at the walls and for symmetry/specular reflection boundaries.…”
Section: Spherical Harmonic Methodsmentioning
confidence: 99%
“…It was found that while the P3 approximation is significantly more accurate than P1, the P5 approximation yields only a slight improvement in accuracy over P3, which is hardly justifiable regarding the increased computational effort. A simplified formulation for 2D axisymmetric problems, which also involves 2( + 1) 4 ⁄ simultaneous partial differential equations, was presented by Ge et al [50], and also implemented in OpenFOAM. Additional refinements of this work were reported by Ge et al [51] who derived a 2D Cartesian version of the higher-order PN method, extended the boundary conditions to allow for nonblack and mixed diffuse-specular surfaces, and to deal with specified radiative flux at the walls and for symmetry/specular reflection boundaries.…”
Section: Spherical Harmonic Methodsmentioning
confidence: 99%
“…1a, FEF was produced by extruding ink in the syringe through the nozzle into the air with the piston movement. Dimensions of the geometrical model of FEF in DIW include: the inner diameter of syringe OpenFOAM is designed as a code for 3D space and defines all meshes as 3D meshes, but wedge type meshes are used for 2D axisymmetric problems specifically [34]. Thus, wedge type meshes were used for the simplified 2D axisymmetric model as shown in Fig.…”
Section: Meshes and Boundary Conditionsmentioning
confidence: 99%
“…The spherical harmonics (P N ) approximation results from expanding the angular intensity as a series of spherical harmonics [5][6][7][8][9][10][11]. The series is then truncated at some point defining the order of the approximation.…”
Section: The Spherical Harmonics Approximationmentioning
confidence: 99%